Agri-food systems in sustainability transition: a systematic literature review on recent developments on the use of the multi-level perspective - Elsner, Friederike; Herzig, Christian; Strassner, Carola (Frontiers in Sustainable Food Systems, 2023)
A sustainability transition (ST) of the agri-food system (AFS) is necessary due to manifold environmental and social exigencies. Scholars widely refer to the multi-level perspective (MLP) in the analysis of those transitions. The fast pace of articles covering AFS transitions, the evolving research on spaces between the three levels, and the consisting unclear conceptualization of MLP levels call for a systematic update on literature utilizing MLP in AFS articles covering ST. As a basis for reporting, this systematic literature review uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The search was conducted on the database Scopus encompassing the period from 2018 to 2022. After the selection procedure, 58 articles were included in the review. We extracted data based on a combination of a concept-driven and data-driven coding scheme. Qualitative research approaches outweigh and interrelated activities within the AFS are being analyzed, predominantly in the agricultural sectors. The focus lays on ongoing transitions. The concept of sustainability and its direction is considered as given (e.g., through the case lens), without further elaborations. The niche constitutes the most prominent object of study and scholars refer to rather socially innovative activities than technological innovations, providing distinct views on radicality and strategies to breakthrough. A space between niche and regime is being presented, with slightly distinct conceptualisations. Actors from both levels collaborate and exert transformative power. The regime is presented as static but also more vividly evolving views on the regime are demonstrated. The landscape receives the least attention and the focus lays on immaterial characteristics. Combinations of MLP with other frameworks have proven useful, for instance, regarding elaborations on the agency on the landscape level. Generally, an unclear conceptualization of regime and landscape persists, lacking a theoretical elaboration. Further research applying MLP should aim for a deeper examination of its theoretical construct, especially in terms of regime and landscape. More quantitative or mixed-methods research could supplement the current dominating qualitative approaches by testing and validating qualitatively constructed theories and phenomena.